Residual stress of 800 MPa high strength steel welded T section: Experimental study. (April 2017) - Cao, Xianlei; Xu, Yong; Kong, Zhengyi; Shen, Hao; Zhong, Wen
Abstract: An experimental study is presented to investigate the residual stress in 800 MPa high strength steel welded T sections using the sectioning method. A total of four different sections with 7 mm thickness steel plates are tested to quantify the magnitude and distribution of both compressive and tensile residual stress. The effect of the width-thickness ratio of web and flange on the distribution of the residual stress is established. The results show the residual stress in all sections is in self-equilibrium. The maximum tensile residual stress locates in the central portion of flange, while the minimum tensile residual stress distributes on both ends of web and flame cutting edges of flange. The maximum tensile residual stress, ranging from 0.43 f y to 0.68 f y, has no obvious relations with the width-thickness ratio of plate. The constant compressive residual stress distributes in the central portion of projecting flange and web. The maximum compressive residual stress, ranging from 0.09 f y to 0.46 f y, decreases as the width-thickness ratio of plate increases, while the area of stress distribution zone increases as the width-thickness ratio of plate increases. A simplified model is suggested for analysis and design based on the magnitude and distribution of residual stress. Highlights: The effect of the width-thickness ratio of web and flange on the distribution of the residual stress is established. The residual stress in all sections is in self-equilibrium. The magnitude and distribution of residual stress distribution are established, and its simplified model is suggested.